2010
DOI: 10.1111/j.1548-1387.2010.01098.x
|View full text |Cite
|
Sign up to set email alerts
|

Speaking through Diabetes:

Abstract: The disproportionate prevalence of Type II diabetes mellitus among the poor suggests that, in addition to lifestyle factors, social suffering may be embodied in diabetes. In this article, we examine the role of social distress in narratives collected from 26 Mexican Americans seeking diabetes care at a public hospital in Chicago. By linking social suffering with diabetes causality, we argue that our participants use diabetes much like an “idiom of distress,” leveraging somatic symptoms to disclose psychologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…These findings suggest that in the Ghanaian context it is important to focus on the subjective as well as the collective experience in health and disease. Psychological models of illness experience must be adapted to research and intervention, alongside sociocultural models (Crossley 2000;Mendenhall et al 2010). …”
Section: Convergences and Divergences Between Lay And Biomedical Theomentioning
confidence: 99%
“…These findings suggest that in the Ghanaian context it is important to focus on the subjective as well as the collective experience in health and disease. Psychological models of illness experience must be adapted to research and intervention, alongside sociocultural models (Crossley 2000;Mendenhall et al 2010). …”
Section: Convergences and Divergences Between Lay And Biomedical Theomentioning
confidence: 99%
“…In our previous ethnographic work, we found both structural violence and interpersonal violence to be major contributors to people’s well-being, in addition to depression specifically (Mendenhall, Seligman et al 2010). This works prompted us to further explore this association in a larger sample, as the relationship of interpersonal abuse and depression is a core concern of psychology and psychiatry, and particularly salient among Mexican-Americans.…”
Section: Introductionmentioning
confidence: 98%
“…We then examine the association between individuals’ past experiences of social stress with depression. We focus on women specifically because our previous work suggested that women of Mexican descent are more likely to experience the prolonged forms of emotional distress linked with depression compared to men (Mendenhall, Seligman et al 2010). The focus on women is important, as well, due to the disproportionate number of women with diabetes who suffer diabetes complications as a result of poor mental health care.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, they have described Hispanic patients’ interpretations and causal understandings of diabetes (Baer, et al 2012; Mendenhall, et al 2010; Smith-Morris 2005), and have identified differences between clinician and patient health beliefs which may lead to different management expectations or clinical miscommunication (Chavez 2004; Hunt, et al 1998a; Maupin and Ross 2012; Weller, et al 2012). Others have examined structural barriers to care which may negatively impact the health of Hispanics, such as inadequate translation services, lack of insurance, undocumented immigrant status and poverty (Becker 2004; Castaneda 2010; Castaneda, et al 2010; Durden and Hummer 2006; Handley and Joseph 2008; Hunt and Voogd 2007).…”
Section: Chronic Illness and Marginalized Populationsmentioning
confidence: 99%